2010
DOI: 10.1007/s10152-010-0213-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive system of the genus Crasiella (Gastrotricha, Macrodasyida)

Abstract: Crasiella diplura from Sweden and Crasiella sp. from Italy were studied alive and with transmission electron microscopy (TEM). The two species are simultaneous hermaphrodites and share the same reproductive system lay-out: paired ovaries extend along the posterior part of the intestine and join mid-dorsally, while bilateral,club-shaped testes lie at the sides of the anterior gut, extending as deferentia that fuse on the mid-ventral plane and open into a single pore; gametes mature in a caudocephalicand centrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Most prominent is a specialized musculature as part of the reproductive system. However, there are also species that contain a caudal organ but obviously lack a specialized musculature like Crasiella fonseci (Hochberg 2014), although congeneric species, e.g., C. diplura, possess such a circular muscle sheath (Guidi et al 2011). (Ruppert 1978a), Tetranchyroderma papii (Hochberg & Litvaitis 2001c), or in Lepidodasys ligni (Hochberg et al 2013).…”
Section: 233)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most prominent is a specialized musculature as part of the reproductive system. However, there are also species that contain a caudal organ but obviously lack a specialized musculature like Crasiella fonseci (Hochberg 2014), although congeneric species, e.g., C. diplura, possess such a circular muscle sheath (Guidi et al 2011). (Ruppert 1978a), Tetranchyroderma papii (Hochberg & Litvaitis 2001c), or in Lepidodasys ligni (Hochberg et al 2013).…”
Section: 233)mentioning
confidence: 99%
“…The morphology of the reproductive organs (male and female gonads, accessory structures such as the frontal and caudal organs, outlet ducts, gland tissues) were studied in quite a lot species of Gastrotricha at the ultrastructural level (e.g., Ruppert & Shaw 1977, Ruppert 1978a, b, 1991, Hummon 1984a-c, Kieneke et al 2008d, 2009, Guidi et al 2011, Todaro et al 2012a The study of Dactylopodola typhle revealed a reproductive system generally comparable to that of other species of the Macrodasyida (Kieneke et al 2008d). However, there are considerable differences as well.…”
Section: Reproductive Organsmentioning
confidence: 99%
“…n., the frontal organ abuts the caudal organ; the circular muscles of the caudal organ are part of the organ itself and therefore independent of the somatic circular muscles anterior to it. How these two organs function together or separately in the uptake of allosperm or release of autosperm, repsectively, is unknown and will likely require a detailed investigation with transmission electon microscopy as has been performed for other macrodasyidan gastrotrichs (e.g., Ruppert 1978, 1991; Guidi et al 2004, 2011; Kieneke et al 2012; Todaro et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we think that ultrastructural studies are needed to conWrm the current information on anatomical organization and function of the putative caudal organ in species of Desmodasys, which so far is based only on light microscopy observations. The study we are calling for is anything but trivial as the presence/absence of a caudal organ has consequences on sperm transfer modality (see e.g., Ruppert 1978;Guidi et al 2011vs. Balsamo et al 2002, which in turn bears potential phylogenetic relevance.…”
Section: Reproductive Anatomy Of Turbanellidaementioning
confidence: 99%
“…In D. mirabilis, spermatogenesis occurs in a caudo-cephalic direction as in most Macrodasyida (Ruppert 1991;Fisher 1994;Guidi et al 2011). Until now, the major steps of the spermatogenetic process have been documented in six species belonging to six major groups: T. cornuta (Turbanellidae: Teuchert 1976), Lepidodasys sp.…”
Section: Reproductive Anatomy Of Turbanellidaementioning
confidence: 99%